Experiences of Visuality in Urban Regeneration Processes between Memory, Participation, and Imagination (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
This article aims to explore the role of the image as a tool for critical reflection and active community participation in urban regeneration practices. To this end, three design initiatives - 10 Porte sul Futuro, Luoghi Dismessi, and Prossima Apertura - implemented in the metropolitan area of Rome and its immediate hinterland have been selected. These projects share a common goal: the cultural and identity-based reappropriation of urban spaces by local communities, in order to re-signify them as meaningful places. The spaces addressed by these projects do not exhibit homogeneous physical or topographical features, but they all express a condition of marginality in contemporary urban living and, consequently, a sense of exclusion or precariousness for those who, in various ways and even for brief periods, ‘inhabit’ them. What unites the three initiatives is their approach: visual installations and iconic works are assigned the role of stimulating new interpretations and proposing alternative narratives for these spaces, so that communities may reinterpret them as places of possibility rather than as residual voids. This approach, implemented through processes of participatory co-design, fosters dialogue between the built environment and its inhabitants, aiming to raise awareness and promote the restoration of essential relationships between city and citizenry. In this context, the article highlights how the diverse characteristics of visual products and the dynamics of citizen engagement contribute to the redefinition of such liminal spaces, transforming them into resources for the community.
Keywords: images; liminal spaces; visual products